La crise yougoslave : la genèse du conflit et ses perspectives de paix dans l'après-Dayton - Fournier, Julie (Études internationales, 1997)
The present article compares the conditions that sparked the Yugoslav conflict and the prospects for peace following the signing of the Dayton Accords. Analysis suggests that the outbreak of nationalist hostilities in Yugoslavia should he explained through a combination of underlying and proximate factors. Just as the circumstances accompanying the collapse of communism were chiefly responsible for the eruption of violence, the immediate factors associated with the Dayton Accords and, more specifically, the attitude of the political elites will determine the likelihood of a lasting peace. Although the new context arising from Dayton seems to have had peace-promoting effects, the socio historical factors that helped to spark the hostilities are still active and are keeping alive the conflict-oriented motives of the local leaders. A resurgence of violence is thus possible.